Rumination variations: aetiology and classification of abnormal behavioural responses to digestive symptoms based on high‐resolution manometry studies. Issue 2 (22nd November 2012) - Tucker, E.; Knowles, K.; Wright, J.; Fox, M. R.
Summary Background Rumination is the voluntary, albeit subconscious return of gastric contents to the mouth. Currently, rumination syndrome and repetitive belching disorders are considered separate diagnoses, as defined by Rome III criteria and high‐resolution oesophageal manometry (HRM). Aim To test the hypothesis that these conditions represent a common behavioural response to aversive digestive stimuli and that successful treatment can be directed at both the stimulus and the response. Methods Case‐note review of consecutive patients with a final diagnosis of behavioural digestive disorders between August 2009 and October 2011. Results Thirty‐five of 46 (76%) patients exhibited 'classical' rumination with abdomino‐gastric strain (R‐waves) driving gastric contents across the lower oesophageal sphincter; 5 (11%) had 'reflux‐related' rumination with R‐waves seen during gastro‐oesophageal common cavity (reflux) events and 6 had (13%) supra‐gastric belching. All received at least one biofeedback session at the time of diagnosis with a good response reported by 20/46 (43%) of the patients, which included 3 with supra‐gastric belching. Additionally, rumination ceased in cases in which definitive treatment relieved the symptoms that triggered abnormal behaviour (e.g. fundoplication in 'reflux‐rumination'). Conclusions Rumination and many of its variations, excluding only some cases of supra‐gastric belching, are associated with abdomino‐gastric strain, a generic abnormal behavioural response to a variety of aversive digestive stimuli. All types of rumination can respond to biofeedback. High‐resolution oesophageal manometry identifies subgroups with distinct mechanisms of disease that respond to specific management targeted at the symptoms that trigger the abnormal behaviour.